URGENSI PENETAPAN ATURAN JASA MAKELAR DALAM TRANSAKSI JUAL BELI TANAH - Cokorda Istri Dian Laksmi Dewi (Magister Hukum Pascasarjana Univeristas Ngurah Rai, 2020)
The relationship between the seller and buyer was between his servoci so that a transaction coul take place an intermediary in a land deal is called a broker. The realtor that supplied her service earned her fee, the arrangement of brokers appears in the statute of commerce and the minister of commerce’s regulation of the company that regulates the magnitude of the broker fee minimal is a 2% and maksimal 5%. But, the regulations can only apply to certified broker, as for the uncertified broker we refer to as the trandisional broker to run the broker function and set it on outside the prevailing rules. For unswer the problem using a normative law research method by using a legals approach and othe regulation to answer about the urgency of a policy on the deployment to a broker. According to the tittle of this post is the urgency ot the brokerage rules in the land deal because if it is not established immediately, it will result in uncontrolled land price or demage to the seller the point of sale to be low after being deducated with the cost of notary, clas tax liability and broker fee.